Development of a Microchip Capillary Electrophoresis Method with Amperometric Detection for Rapid and Simultaneous Analysis of Ascorbic Acid and Glutathione in Antioxidant Cocktail Injection Preparations - Nina Irmayanti Harahap (CV. Get Press Indonesia, 2025)
Antioxidant cocktail injections containing ascorbic acid (AA) and glutathione (GSH) require precise and reliable analytical methods to ensure product safety and therapeutic consistency. Conventional methods such as HPLC tend to be time-consuming, require a large number of reagents, and are less suitable for rapid pharmaceutical quality control or at production sites. This study aimed to develop and validate a microchip capillary electrophoresis with amperometric detection (MCE-AD) method for the simultaneous quantification of AA and GSH in injectable preparations. Method optimization included the selection of running buffer, voltage, sample injection parameters, and detection potential to achieve stable separation and optimal electrochemical response. The validated method showed excellent linearity over the concentration range of 1–150 mg/L for AA and 2–200 mg/L for GSH, with correlation coefficients of 0.9989 and 0.9991, respectively. The detection limits were recorded at 0.42 mg/L for AA and 0.61 mg/L for GSH, while the quantification limits were 1.39 mg/L and 2.04 mg/L, respectively. Precision testing yielded a %RSD of <3%, and accuracy testing demonstrated recoveries between 97–103%. Analysis of commercial injection samples demonstrated compliance with pharmacopoeial requirements, supporting the practical application of this method. With an analysis time of <60 seconds and very low sample consumption (<10µL per analysis), the developed MCE-AD technique provides a rapid, economical, and reliable alternative to conventional analytical platforms. These findings confirm the suitability of the method for routine quality testing and its potential integration into portable and automated pharmaceutical analysis systems.